2014
DOI: 10.1136/annrheumdis-2013-204572
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography assessment of large vessel inflammation in patients with newly diagnosed, biopsy-proven giant cell arteritis: a prospective, case–control study

Abstract: Background Positron emission tomography (PET) scan is emerging as a promising imaging technique to detect large-vessel inflammation in giant cell arteritis (GCA). However, the lack of a standardised definition of arteritis based on 18 fluorodeoxyglucose (FDG) uptake is an important limitation to the use of PET scan for diagnostic purposes. Objective To prospectively assess the intensity and distribution of FDG uptake at different vascular territories in patients with newly diagnosed GCA compared with controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(85 citation statements)
references
References 19 publications
3
72
1
8
Order By: Relevance
“…In this setting, the noninvasive and early evaluation of the inflammatory process given by PET/CT represents an added value for rheumatologists [12]; the possibility to get baseline information about disease evolution would be surely as much important for clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, the noninvasive and early evaluation of the inflammatory process given by PET/CT represents an added value for rheumatologists [12]; the possibility to get baseline information about disease evolution would be surely as much important for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the extent of the disease/involvement of extracranial sites 4. The evaluation of therapy response [9][10][11][12][13][14][15][16][17][18][19] On the basis of cumulated report accuracy, primary evaluation of LVV is now considered a major indication for 18 F-FDG PET/CT in non-oncological patients [20]. Some issues, however, have not been fully analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the utility of the 18 F-FDG PET/CT scan in the assessment of disease activity in patients with LVV (27)(28)(29)(30)(31)(32). Notwithstanding the lack of standardization and heterogeneous reference standards, 18 F-FDG PET/ CT has a substantial sensitivity and specificity for the diagnosis of both TAK and GCA (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Prieto-González et al [42] recently found that FDG uptake by large vessels, including aorta, has a high sensitivity and specificity for the diagnosis of GCA. They showed that the maximal standardized uptake value (SUVm) correlated with acute phase reactants and serum IL-6 levels.…”
Section: Discussionmentioning
confidence: 98%